2018
DOI: 10.1111/jcmm.14109
|View full text |Cite
|
Sign up to set email alerts
|

Granulocytic myeloid‐derived suppressor cell population increases with the severity of alcoholic liver disease

Abstract: Alcoholic liver disease ( ALD ) is a progressive liver disease that can cause a series of complications, including cirrhosis, liver failure and hepatocellular carcinoma. Granulocytic myeloid‐derived suppressor cell ( gMDSC ) populations have been observed to expand in various liver diseases and to inhibit innate and adaptive immunity in patients with liver disease. However, the characteristics of gMDSC s in patients with ALD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
(86 reference statements)
1
7
0
Order By: Relevance
“…It was earlier reported that M-MDSCs suppressed T-cell functions and antimicrobialspecific innate immune responses in ACLF patients (26). An increase in peripheral and intrahepatic G-MDSC populations was reported in ALC (Alcoholic liver cirrhosis) patients (27). In our study, we also found a significant increase in MDSCs, especially G-MDSCs, in cirrhosis patients with sepsis.…”
Section: Discussionsupporting
confidence: 81%
“…It was earlier reported that M-MDSCs suppressed T-cell functions and antimicrobialspecific innate immune responses in ACLF patients (26). An increase in peripheral and intrahepatic G-MDSC populations was reported in ALC (Alcoholic liver cirrhosis) patients (27). In our study, we also found a significant increase in MDSCs, especially G-MDSCs, in cirrhosis patients with sepsis.…”
Section: Discussionsupporting
confidence: 81%
“…Accumulating evidence indicates that gMDSC play an important role in the development of microbial infections, autoimmune disorders, and cancer. The gMDSC population is elevated in patients with alcoholic liver disease and closely associated with disease progression ( 9 ). However, we know little regarding whether gMDSC have impaired antimicrobial response or phagocytic capacity in patients with HBV-ACLF.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between MDSCs and coagulation indexes has also been reported in other diseases. In alcoholic liver cirrhosis patients, level of plasma ARG-1 secreted by MDSCs were correlated with INR ( 33 ). In adult acute myeloid leukemia patients, MDSCs were significantly increased, and the level of MDSCs was correlated well with plasma D-dimer levels ( 34 ).…”
Section: Discussionmentioning
confidence: 99%